The Adiwiyata Islamic Boarding School Management (A Study of Participatory Leadership Style) - Muhammad Anggung Manumanoso Prasetyo; Bashori Bashori; Auliya Rahmi (AT-TA'LIM, 2021)
In Aceh Province, Dayah Perbatasan Darul Amin is an Islamic Boarding school institution that has twice had achievement as the cleanest and healthiest boarding school as part of adiwiyata-based education institution concept. Such achievement by the Islamic boarding school can inspire and terminate a syndrome that a boarding house is a slump, dirty and unhealthy place. Also, it can change the public paradigm that boarding school is a very representative place to study. This research analyzes the Islamic boarding school management model in implementing the adiwiyata concept through participative leadership. The research approach paradigm is the qualitative one. The research used a diary method (DM). This article is an experience of Darul Amin Islamic Boarding School in implementing the adiwiyata program by implementing an effective Islamic boarding school. Results of the research show that adiwiyata program management is conducted through participative leadership, namely (1) formulation of adiwiyata Islamic boarding school, (2) building intern consolidation, (3) implementation of cleanliness management, (4) procurement of necessary infrastructure, (5) program evaluation and (6) organizational development. All elements' active contribution in realizing the adiwiyata Islamic boarding school can improve students' characteristics to live clean and love their environment. The participative leadership of the Kyai is proven to be able to improve the effectiveness of adiwiyata Islamic boarding school management.